The Effect of Android Game Based Learning for Student Interest in Mathematics Learning - Laksita, Ghany Desti; Oktaviani, Dewi; Pangestu, Aji (Proceeding International Conference on Science and Engineering, 2020)
Nowadays technology is growing very rapidly. The existence of this technology development, helps a lot of people in carrying out their activities. There is one form of development technology that very influential in everyday life and mostly found in the community is an android smartphone. In this age, smartphones have become a lifestyle for the society. The development of smartphone technology has been perceived by all levels of society especially for students. Besides, being used in social media, smartphone purpose is also being used to play a game by students, both online and offline games. In the field of education, smartphones are still rarely used to support learning activities, especially in mathematics learning. This issue is happened because there are still many educators who are reluctant to switch from conventional learning methods to digital-based learning. Even though the interest of students in the smartphone technology especially game, is high enough. This research, intend to determind the effect of mathematics learning based on interactive android game to student’s study interest. This research use study literature method, that is consider relevant various research, then the researcher conclude it based on the various research. The result of this research is there is an influence of learning based on interactive android game to student’s interest. So, this learning based on android game can be used to increase student interest in mathematics.